Central Banks’ Response to the Current Financial Crisis – Between Costs and Benefits - Teodora Cristina Barbu (International Journal of Economics and Financial Issues, 2012)
Our study is inserted in the thematic area dedicated, during recent years, to the research on central banks’ response to financial crisis. The global financial crisis has outlined a series of weaknesses located at regulatory and supervisory activities’ level, causing major central banks to face a new operating environment, in which traditional monetary policy tools are ineffective (key interest rate close to zero) in restoring the financial markets’ proper functioning. The unconventional monetary policy measures, the dramatic fall of the key interest rate, the balance sheet structure modification and extension of collateral accepted by central banks are the main issues on which we focused our attention, to highlight the costs and benefits recorded by these institutions. All major central banks have implemented highly innovative, flexible facilities and the main beneficiaries have been the banking systems in their entirety.